Cobalt-Catalyzed Oxidative [4+2] Annulation of Benzamides with Dihydrofuran: A Facile Route to Tetrahydrofuro[2,3-c]isoquinolinones - Zhang, Zhuo-Zhuo; Zhou, Gang; Huang, Fan-Rui; Shi, Bing-Feng (Synthesis, 2021)
A cobalt-catalyzed oxidative [4+2] annulation of benzamides with dihydrofuran was developed for the expeditious synthesis of tetrahydrofuro[2,3-c]isoquinolinones. Commercially available and inexpensive Co(OAc)2·4H2O was used as an efficient catalyst. Various functional groups were tolerated, affording the desired products in good yields with excellent regioselectivity and good diastereoselectivity under mild conditions.
Keywords: cobalt; oxidative annulations; C–H activation; tetrahydrofuro[2,3-c]isoquinolinone; dihydrofuran